(untitled) (International Journal of Physiotherapy, 2025)
Background: Thoracic and abdominal procedures have a higher incidence of postoperative pulmonary problems, which range from 12% to 70%. Between 45% and 85% of patients may experience it. It is well known that abdominal surgery affects the way the breathing muscles work both during and after the procedure. This study aimed to assess and compare the effectiveness of conventional physiotherapy and OPEP (Vibrapep) in patients recovering from open abdominal surgeries. Method: A comparative study was performed with 36 patients aged 20 to 60 who underwent open abdominal surgery. The participants were divided into two groups. Assessments included maximal inspiratory pressure, chest expansion measurements, and peak expiratory flow. Group A received Vibrapep alongside standard exercises, whereas Group B underwent conventional exercises. The intervention was conducted twice daily for five days. Results: Statistical analysis was done using SPSS 23. The within-group analysis showed that both groups made statistically significant improvements in all parameters except at the xiphoid and T4 levels (p>0.05). However, the experimental group was more effective in improving secretion clearance, thoracic expansion, maximal inspiratory pressure, and peak expiratory rate as depicted by significant differences (p<0.05). Conclusion: The study concluded that Vibrapep is an effective adjunct to conventional physiotherapy in bronchial hygiene therapy for patients recovering from open abdominal surgeries. Its use demonstrated significant improvements in sputum clearance, pulmonary function, and thoracic expansion, highlighting its potential as a valuable therapeutic device in postoperative respiratory care.